TRANSFORMASI PERAN HUMAS DI ERA DIGITAL : PEMANFAATAN MEDIA SOSIAL DALAM MEMBANGUN CITRA PONDOK PESANTREN M. BASIUNI IMRAN DI KABUPATEN SAMBAS - Setiawan, Halim (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
The transformation of digital technology has changed the way public relations (PR) operates in various institutions, including the M. Basiuni Imran Islamic boarding school. This research aims to explore the use of social media as a strategic tool in building and strengthening the image of the M. Basiuni Imran Islamic boarding school. Using a descriptive qualitative approach, data was collected through interviews and observing Islamic boarding school social media activities. The research results show that digital public relations plays an important role in creating interesting and relevant content, as well as interacting directly with the public through various platforms such as YouTube, Tik Tok, Instagram and Facebook. In addition, the findings indicate that the use of social media not only makes it easier to disseminate information, but also increases transparency and public trust in Islamic boarding schools. Through social media, the M. Basiuni Imran Islamic boarding school can strengthen relationships with the surrounding community and expand the reach of the programs they offer. Thus, Islamic boarding school public relations that is adaptive to digital technology can contribute significantly to building a positive image and relevance of educational institutions in the modern era.